First names and surnames of the Guarani and Kaiowá from Mato Grosso do Sul - Silva Martins, Andérbio Márcio (2020)
Guarani and Kaiowá names and surnames have a historical origin from contact with European settlers. Gradually, traditional names are going into disuse from a social point of view, but their permanence from a religious point of view as a kind of protection remain. In this article, we present a survey of the civil names of indigenous guarani and kaiowá teachers who passed through the Indigenous Intercultural Degree – Teko Arandu, Federal University of Grande Dourados - UFGD, Mato Grosso do Sul. The survey was conducted from the Teacher's Class Control System. Then, in the light of historical and social facts, we present the social functions of the names today and postulate the possible origins of surnames, considering the process of colonization that these peoples went through. The results of the study do not cover the origin of surnames in their individuality, but present an overview of the historical and social conditions that could give conditions to the existence of this new way of naming and indicating family belonging among the Guarani and Kaiowá indigenous peoples of the southern cone of Mato Grosso do Sul. Keywords: Guarani; Kaiowá; Anthroponomical, Socioanthropomonatic.